Isolation of Klebsiella pneumoniae and Acinetobacter baumannii from street vended cut fruits sold in Dhaka city of Bangladesh and their antibiotic susceptibility pattern - Farid(Safa), Saima Binta; Prami, Afrida Nawer (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.